Changes in coagulation parameters in polytrauma patients with different body mass index according to the enoxaparin-sodium dosing strategy under conventional versus restrictive fluid therapy regimens - М.О. Gogiya; S.V. Kursov; О.V. Markov; O.М. Kudrevych (Journal of V. N. Karazin Kharkiv National University: Series Medicine, 2025)
Background. Coagulopathy associated with fluid resuscitation and disseminated intravascular coagulation constitutes a devastating complication of polytrauma, leading to the development of multiple organ dysfunction syndrome.